Peculiarities of Goods Consumption in Kazakhstan Amidst a Crisis - Dulatbekova, N.; Tulembayeva, A.; Pak, E. (Karagandy University of the name of acad. E.A. Buketov, 2024)
Object: Consumer behavior in the Republic of Kazakhstan takes the spotlight of this article. While primarily focusing on a period between 2019 and 2022, to give a better idea of the context, the study also pulls data from a wider time interval from 2011 to 2022. This research pays careful attention to inflation, real salaries, and total household consumption. Methods: The article offers various macroeconomic indicators. To level out bias in statistics caused by inflation, we calculated a deflator. Another important aspect taken into question was inflation rate between 2020 and 2022 in the context of various categories of goods. Findings: We have revealed a negative trend obstructing the growth of real GDP per capita, making it slower than consumption, which is potentially problematic for the social debt burden and may bring about economic problems on a national scale. This assumption is confirmed by the growth in bank lending. Conclusions: Our results provide valuable insights into consumer behavior in the context of rising inflation and salary changes in Kazakhstan. These findings might prove useful for the entire business community, government agencies, and researchers. Our research can also be used for developing marketing strategies and managerial decision-making.
Object: Consumer behavior in the Republic of Kazakhstan takes the spotlight of this article. While primarily focusing on a period between 2019 and 2022, to give a better idea of the context, the study also pulls data from a wider time interval from 2011 to 2022. This research pays careful attention to inflation, real salaries, and total household consumption. Methods: The article offers various macroeconomic indicators. To level out bias in statistics caused by inflation, we calculated a deflator. Another important aspect taken into question was inflation rate between 2020 and 2022 in the context of various categories of goods. Findings: We have revealed a negative trend obstructing the growth of real GDP per capita, making it slower than consumption, which is potentially problematic for the social debt burden and may bring about economic problems on a national scale. This assumption is confirmed by the growth in bank lending. Conclusions: Our results provide valuable insights into consumer behavior in the context of rising inflation and salary changes in Kazakhstan. These findings might prove useful for the entire business community, government agencies, and researchers. Our research can also be used for developing marketing strategies and managerial decision-making.
Keywords: wages; consumer behavior; economic instability; pandemic; inflation; consumption; crisis; Дағдарыс жағдайы; Дағдарыс; Қазақстан халқы; Қазақстан; тауарлар; тұтыну ерекшеліктері; тұтыну; ерекшеліктер; жалақы; сатып алу тәртібі; дағдарыс; экономикалық тұрақсыздық; пандемия; пандемия; инфляция; тұтыну; дағдарыс; Особенности потребления; Особенности; потребление товаров; население Казахстана; население; Казахстан; условия кризиса; кризис; потребление; экономическая нестабильность; покупательское поведение; заработная плата